Surface modification bonding strength improving method based on bionic gecko foot surface structure
Through laser technology, the bonding surfaces of CFRP and aluminum alloys are treated imitate the surface structure of the gecko foot, which solves the problem of low bonding strength of the overlap bonding joints, and achieves higher bonding strength and moisture-heat resistance.
Patent Information
- Application Number
- CN202510084034.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Lap bonding joints are prone to interface failure during tensile breakage, resulting in low bonding strength, limiting their promotion and application in high reliability scenarios.
The adhesive surface of CFRP and aluminum alloy is surface treated by laser technology to prepare the bonding morphology of the surface structure of the gecko foot, increasing the contact area of the adhesive and mechanical interlocking effect.
It significantly improves the bonding strength and resistance to environmental moisture and heat erosion of the overlap joint, extends the service life of the joint, and improves its application performance in high reliability scenarios.
Smart Images

Figure CN119589971A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface modification bonding strength improvement method based on a gecko foot-imitation surface structure, and belongs to the technical field of lap joint bonding processes. Background Art
[0002] Carbon fiber reinforced composites (CFRP) and aluminum alloys have been widely used in aerospace, automobile manufacturing and other fields due to their excellent lightweight and high strength properties. However, due to the significant differences in the surface chemical properties and microstructures of the two materials, lap joints are often prone to interfacial failure during tensile fracture, resulting in low bonding strength, which limits their further promotion and application in high-reliability scenarios.
[0003] The surface of the gecko-foot structure is precisely controlled by laser parameters (such as power, line spacing and scanning speed) to generate an interface morphology with micro-nanoscale roughness. This rough structure can effectively improve the wettability of the bonding surface, allowing the liquid adhesive to fully spread on the surface and penetrate into the microscopic depressions, thereby increasing the contact area and significantly improving the mechanical locking effect and interfacial bonding strength of the bonding. This method is simple and efficient, and can provide excellent interface conditions for subsequent bonding processes.
[0004] In addition, the gecko-foot-like structure can also form super-hydrophobic characteristics on the interface surface, thereby improving the resistance of the bonding interface to environmental factors (such as moisture or pollutants). This super-hydrophobicity effectively delays moisture intrusion and corrosion by reducing the retention area of liquid on the interface, providing additional protection for the bonding interface. In practical applications, this feature helps to extend the service life of the bonded joint and further improve its environmental adaptability. Summary of the invention
[0005] The present invention designs and develops a surface modification bonding strength improvement method based on the surface structure imitating the gecko foot. The bonding surface is laser processed by a laser process, so that the bonding strength of the lap joint can be improved.
[0006] Another purpose of the present invention is to control the engraving parameters during the laser engraving process so that the adhesive can fully infiltrate the bonding surface, increase the contact area to form mechanical interlocking, and improve the bonding strength.
[0007] The technical solution provided by the present invention is:
[0008] A method for improving bonding strength of a surface modified by imitating the surface structure of a gecko's foot, comprising:
[0009] Step 1: Perform the first impurity removal pretreatment on the CFRP sheet and the aluminum alloy sheet;
[0010] Step 2: laser engraving the bonding surfaces of the CFRP sheet and the aluminum alloy sheet after impurities removal respectively using a laser engraving machine to obtain the CFRP sheet and the aluminum alloy sheet with the bonding surface morphology of the gecko foot-like surface structure; and performing a second impurity removal treatment;
[0011] Among them, during laser engraving, the power of the laser engraving machine is 2.5W~27W, the speed is 100mm / s~1000mm / s, and the laser line spacing is 50μm~150μm; the ablation area on the CFRP plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm; the ablation area on the aluminum alloy plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm;
[0012] Step 3: Perform secondary impurity removal treatment on the obtained plate, and evenly distribute multiple glass beads on the treated bonding surface. During the distribution of the glass beads, preliminary fixation is required to fix the glass beads to the bonding surface;
[0013] Step 4: Evenly apply the adhesive on the bonding surface with glass beads, and fit the two bonding surfaces together. After fitting, use a clamp to position and press the bonding plates, wipe off the excess adhesive that has overflowed, and put the clamp and the plates into a drying oven for curing. After curing, cool to room temperature to obtain a finished lap joint.
[0014] Preferably, the first impurity removal pretreatment and the second impurity removal pretreatment have the same process, both comprising:
[0015] After wiping the CFRP sheet and the aluminum alloy sheet with acetone solution, they were placed in an ultrasonic cleaner and cleaned with deionized water at a constant temperature of 25°C for 10 to 15 minutes. They were then placed in a drying oven and dried at 80°C for 30 to 60 minutes until the water was completely evaporated. After drying, the sheets were naturally cooled to room temperature.
[0016] Preferably, the CFRP plate is a sixteen-layer stacked structure, comprising:
[0017] Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber;
[0018] Wherein, in the unidirectional carbon fiber layer, the carbon fiber is T300 grade;
[0019] 3k twill carbon fiber is a FAW200 epoxy resin matrix with a matrix volume fraction of 40% and a carbon fiber volume fraction of 60%;
[0020] The unidirectional carbon fiber is a FAW150 epoxy resin matrix with a matrix volume fraction of 37% and a carbon fiber volume fraction of 63%.
[0021] Preferably, the CFRP plate is prepared by a hot pressing process, comprising:
[0022] Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber were autoclaved at a temperature of 160°C and a pressure of 20kg / cm 2 Press for 30 min under the conditions of
[0023] The aluminum alloy plate is made by anodizing A6061-T6 aluminum alloy in a 10% H2SO4 solution at a voltage of 12V for 30 minutes.
[0024] Preferably, the diameter of the glass beads is the same as the thickness of the required adhesive layer, and the error cannot exceed ±0.2 mm;
[0025] The total volume of all the glass beads cannot exceed 4% of the total volume of the glue layer.
[0026] Preferably, the adhesive in step 4 is a two-component epoxy adhesive, including a matrix resin and a curing agent, which are mixed in a mass ratio of 100:40.
[0027] Preferably, the preliminary fixing method in step three includes: preliminarily fixing the glass beads to the bonding surface by electrostatic adsorption or a light adhesive.
[0028] Beneficial effects of the present invention: The surface modification bonding strength enhancement method based on the surface structure of the gecko's foot provided by the present invention uses a simple and precise laser process to perform surface treatment on the bonding surface of CFRP and aluminum alloy, and prepares the bonding morphology of the surface structure of the gecko's foot by controlling the laser power, line spacing and speed. The morphology not only has a high surface roughness, but also has a high wettability, which allows the adhesive to fully infiltrate the bonding surface, increase the contact area to form a mechanical interlock, and thus improve the bonding strength.
[0029] The method has a simple processing process, can improve the bonding strength and resistance to environmental moisture and heat corrosion of the lap joint, and has high practical value in the material bonding direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a gecko-foot-like surface structure morphology diagram of the bonding surface described in the present invention.
[0031] Figure 2 The present invention is a schematic flow chart of the surface modification and bonding strength enhancement method based on the gecko-foot-mimicking surface structure.
[0032] Figure 3 This is a schematic diagram of the dimensions of the single lap joint described in the present invention.
[0033] Figure 4This is a SEM image of the CFRP bonding surface after laser scanning according to the present invention.
[0034] Figure 5 This is a SEM image of the aluminum alloy bonding surface after laser scanning described in the present invention.
[0035] Figure 6 This is a schematic diagram comparing the moisture and heat resistance of a material before and after laser treatment according to the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0037] like Figure 1-6 As shown, the present invention provides a surface modification bonding strength improvement method based on the surface structure of the gecko foot, which can improve the bonding strength of the lap joint by laser processing the surface to be bonded through a laser process, including:
[0038] Step 1: Perform the first impurity removal pretreatment on the CFRP sheet and the aluminum alloy sheet;
[0039] Among them, the CFRP plate is a sixteen-layer stacked structure, including:
[0040] Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber;
[0041] In the unidirectional carbon fiber layer, the carbon fiber is T300 grade;
[0042] CFRP sheets are prepared by hot pressing process, including:
[0043] Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber were autoclaved at a temperature of 160°C and a pressure of 20kg / cm 2 Press for 30 min under the conditions of
[0044] The aluminum alloy plate is made by anodizing A6061-T6 aluminum alloy in a 10% mass concentration H2SO4 solution at a voltage of 12V for 30min;
[0045] 3k twill carbon fiber is a FAW200 epoxy resin matrix, the matrix volume fraction is 40%, and the remaining 60% is the carbon fiber volume fraction;
[0046] The unidirectional carbon fiber is a FAW150 epoxy resin matrix, the matrix volume fraction is 37%, and the remaining 63% is the carbon fiber volume fraction.
[0047] Step 2: laser engraving the bonding surfaces of the CFRP sheet and the aluminum alloy sheet after impurities removal respectively using a laser engraving machine to obtain the CFRP sheet and the aluminum alloy sheet with the bonding surface morphology of the gecko foot-like surface structure; and performing a second impurity removal treatment;
[0048] Among them, during laser engraving, the power of the laser engraving machine is 2.5W~27W, the speed is 100mm / s~1000mm / s, and the laser line spacing is 50μm~150μm; the ablation area on the CFRP plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm; the ablation area on the aluminum alloy plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm;
[0049] Step 3: Perform secondary impurity removal treatment on the obtained plate, and evenly distribute multiple glass beads on the treated bonding surface. During the distribution of the glass beads, it is necessary to initially fix the glass beads to the bonding surface by electrostatic adsorption or light adhesive;
[0050] In the present invention, as a preferred embodiment, 3M TM Super 77 TM Multi-purpose spray adhesive initially fixes the glass beads to the bonding surface.
[0051] The first impurity removal pretreatment and the second impurity removal pretreatment process are the same, both comprising:
[0052] After wiping the CFRP sheet and the aluminum alloy sheet with acetone solution, they were placed in an ultrasonic cleaner and cleaned with deionized water at a constant temperature of 25°C for 10 to 15 minutes. They were then placed in a drying oven and dried at 80°C for 30 to 60 minutes until the water was completely evaporated. After drying, the sheets were naturally cooled to room temperature.
[0053] The diameter of the glass beads should be the same as the thickness of the required adhesive layer, and the error should not exceed ±0.2mm;
[0054] And the sum of the volumes of all the glass beads cannot exceed 4% of the total volume of the glue layer.
[0055] Step 4: Evenly apply the adhesive on the bonding surface with glass beads, and fit the two bonding surfaces together. After fitting, use a clamp to position and press the bonded plates, wipe off the excess adhesive that has overflowed, and put the clamp and the plates into a drying oven for curing. After curing, cool to room temperature to obtain a lap joint with stable mechanical properties.
[0056] In the present invention, as a preferred embodiment, the adhesive is a two-component epoxy adhesive Araldite 2015, including a matrix resin and a curing agent, which are mixed in a mass ratio of 100:40. The adhesive needs to be fully stirred before coating to ensure the uniformity of the components, and the lap joint surface is kept dry and clean before bonding to ensure the bonding quality.
[0057] Example
[0058] Taking T300 grade 3k twill carbon fiber and A6061-T6 aluminum alloy as an example, the bonding surface is processed into a surface structure morphology imitating the gecko's foot by laser technology, and it is applied in practice. The specific implementation steps are as follows:
[0059] The first step is to prepare T300 grade 3k twill carbon fiber 1 and A6061-T6 aluminum alloy 2.
[0060] The CFRP matrix is composed of 3k twill (2 layers) and unidirectional (14 layers) carbon fiber (T300 grade). The 3k twill carbon fiber and unidirectional carbon fiber use FAW200 and FAW150 epoxy resin matrices, respectively, with matrix volume fractions of approximately 40% and 37%, respectively. The CFRP is made up of a total of 16 layers and is prepared by hot pressing at 160°C, 20kg / cm 2 Press under pressure for 30 minutes.
[0061] The A6061-T6 aluminum alloy was anodized in a 10% mass concentration H2SO4 solution at a voltage of 12 V for 30 minutes.
[0062] In the second step, the CFRP and aluminum alloy were wiped clean with acetone solution, placed in an ultrasonic cleaner and cleaned with deionized water at 25°C for 15 minutes, and then immediately placed in a drying oven at 80°C for 60 minutes and cooled to room temperature. The laser engraving machine was used to set the parameters of laser power (P), laser line spacing (H D ) and laser speed (V) as shown in Table 1; the arc radius is selected as 85μm to treat the bonding surface of the materials respectively, and obtain CFRP and aluminum alloy with the bonding surface morphology of gecko feet. Then wipe it clean again with acetone solution, put it in an ultrasonic cleaner and use deionized water to clean it at a constant temperature of 25℃ for 10-15min, then immediately put it in a drying oven at 80℃ for 60min and cool it to room temperature.
[0063] In the third step, a confocal laser microscope (CLM, VK-X3000, KEYENCE) and a contact angle meter (CAME, 100SB, Sindatek) were used to measure the surface roughness and surface wettability of the bonding surfaces of CFRP and aluminum alloy under different laser parameter treatments, and the optimal parameter group with the maximum surface roughness (Ra) and the minimum surface water contact angle (WCA) was selected. The test showed that the optimal parameters were CFRP: 27W, 50μm, 100mm / s; aluminum alloy: 27W, 100μm, 100mm / s;
[0064] Step 4: Prepare adhesive 3.
[0065] The adhesive is a two-component epoxy adhesive Araldite 2015, in which component A is the matrix resin and component B is the curing agent, which are evenly mixed in a mass ratio of 100:40 before use. The adhesive needs to be fully stirred before coating to ensure the uniformity of the components, and the faying surface should be kept dry and clean before bonding to ensure the bonding quality.
[0066] The fifth step is to apply an appropriate amount of adhesive to the bonding surface of the CFRP and aluminum alloy substrate of the optimal parameter group, and align them in a predetermined position to ensure that the bonding surface is completely fitted. A special clamp is used during the bonding process. By tightening the spiral push rod, the thickness of the adhesive is adjusted to about 0.2mm. Press and cure at room temperature for 24 hours to ensure that there are no bubbles or gaps between the bonding surfaces. Put the bonding assembly in a drying oven and cure it at 80°C for 60 minutes to ensure that the adhesive is completely cured. After the curing is completed, the joint is naturally cooled to room temperature to obtain a lap joint with stable mechanical properties.
[0067] A comparative example was prepared, in which the bonding surface of the comparative example was not laser treated, and other treatments and bonding methods were consistent with those of the embodiment.
[0068] The optimal parameter embodiment and the comparative example were placed in a damp heat aging environment box for damp heat aging test, and the aging process was as follows: (1) the temperature was raised to 70±2°C within 30 minutes (this step is only required in the first cycle); (2) the temperature was maintained at 70±2°C within 5 hours±20 minutes, while the relative humidity was maintained above 90%; (3) the temperature was reduced to -40±3°C within 60±20 minutes; (4) the temperature was maintained at -40±3°C within 5 hours±20 minutes; (5) the temperature was raised to 70±2°C within 60±20 minutes; (6) steps (2) to (5) were repeated.
[0069] The aging time of the test samples was 1 to 8 weeks, and then the tensile failure test was carried out using an electronic universal testing machine to obtain the joint failure load data. The results are as follows: Figure 6 shown.
[0070] The CFRP sheet and aluminum alloy sheet joints that have not been treated with the gecko foot-like treatment are taken as comparison examples.
[0071] The bonding strength between the CFRP sheet and the aluminum alloy sheet treated with the imitation gecko foot was greatly improved. Compared with the untreated joint strength (9.19±0.16MPa), the joint strength after the imitation gecko foot treatment (10.4±0.32MPa) increased by 13.17%. After 8 weeks of aging test, the lap shear strength of the untreated and imitation gecko foot surface structure CFRP / aluminum alloy specimens decreased to 2.22±0.82MPa and 9.26±0.29MPa, respectively. Compared with the unaged specimens, the lap shear strength of the untreated specimens decreased by 75.84%, and the lap shear strength of the imitation gecko foot surface structure decreased by 10.96%, which greatly increased the service life of the joints.
[0072] Table 1
[0073]
[0074] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for improving the bonding strength of a surface modified by imitating the surface structure of a gecko's foot, characterized in that: include: Step 1: Perform the first impurity removal pretreatment on the CFRP sheet and the aluminum alloy sheet; Step 2: laser engraving the bonding surfaces of the CFRP sheet and the aluminum alloy sheet after impurities removal respectively using a laser engraving machine to obtain the CFRP sheet and the aluminum alloy sheet with the bonding surface morphology of the gecko foot-like surface structure; and performing a second impurity removal treatment; Among them, during laser engraving, the power of the laser engraving machine is 2.5W~27W, the speed is 100mm / s~1000mm / s, and the laser line spacing is 50μm~150μm; the ablation area on the CFRP plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm; the ablation area on the aluminum alloy plate is a plurality of arc-shaped parallel curves, the radius of the arc is 85μm, and the spacing between each two adjacent arcs is 20μm; Step 3: Perform secondary impurity removal treatment on the obtained plate, and evenly distribute multiple glass beads on the treated bonding surface. During the distribution of the glass beads, preliminary fixation is required to fix the glass beads to the bonding surface; Step 4: Evenly apply the adhesive on the bonding surface with glass beads, and fit the two bonding surfaces together. After fitting, use a clamp to position and press the bonding plates, wipe off the excess adhesive that has overflowed, and put the clamp and the plates into a drying oven for curing. After curing, cool to room temperature to obtain a finished lap joint.
2. The surface modification bonding strength enhancement method based on the gecko foot-like surface structure according to claim 1 is characterized in that: The first impurity removal pretreatment and the second impurity removal pretreatment process are the same, both comprising: After wiping the CFRP sheet and the aluminum alloy sheet with acetone solution, they were placed in an ultrasonic cleaner and cleaned with deionized water at a constant temperature of 25°C for 10 to 15 minutes. They were then placed in a drying oven and dried at 80°C for 30 to 60 minutes until the water was completely evaporated. After drying, the sheets were naturally cooled to room temperature.
3. The surface modification bonding strength enhancement method based on the gecko foot-like surface structure according to claim 2, characterized in that: The CFRP plate has a sixteen-layer stacked structure, including: Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber; Wherein, in the unidirectional carbon fiber layer, the carbon fiber is T300 grade; 3k twill carbon fiber is a FAW200 epoxy resin matrix with a matrix volume fraction of 40% and a carbon fiber volume fraction of 60%; The unidirectional carbon fiber is a FAW150 epoxy resin matrix with a matrix volume fraction of 37% and a carbon fiber volume fraction of 63%.
4. The method for improving the bonding strength of a surface modified by imitating the surface structure of a gecko's foot according to claim 2, characterized in that: The CFRP plate is prepared by a hot pressing process, comprising: Two layers of 3k twill carbon fiber and fourteen layers of unidirectional carbon fiber were autoclaved at a temperature of 160°C and a pressure of 20kg / cm 2 Press for 30 min under the conditions of The aluminum alloy plate is made by anodizing A6061-T6 aluminum alloy in a 10% H2SO4 solution at a voltage of 12V for 30 minutes.
5. The method for improving the bonding strength of a surface modified by imitating the surface structure of a gecko's foot according to claim 4, characterized in that: The diameter of the glass beads is the same as the thickness of the required adhesive layer, and the error cannot exceed ±0.2mm; The total volume of all the glass beads cannot exceed 4% of the total volume of the glue layer.
6. The method for improving the bonding strength of a surface modified by imitating the surface structure of a gecko's foot according to claim 5, characterized in that: The adhesive in step 4 is a two-component epoxy adhesive, including a matrix resin and a curing agent, which are mixed in a mass ratio of 100:
40.
7. The method for improving the bonding strength of a surface modified by imitating the gecko foot surface structure according to claim 6, characterized in that: The preliminary fixing method in step three includes: preliminarily fixing the glass beads to the bonding surface by electrostatic adsorption or light adhesive.
Citation Information
Patent Citations
Super-hydrophobic material and preparation method thereof
CN102950099A
Bionic surface applied to miniature crawling robot and preparation method of bionic surface
CN116653188A
Method for enhancing bonding interface of porous metal sandwich panel
CN117363288A
Composites with controllable superhydrophilic and superhydrophobic interface performances, a 3D printing method and 3D printed parts
US20230415407A1
Stress and texture morphology controlling method for preparing super-hydrophobic surface of aluminum alloy by laser etching
US20240042552A1